METODE IJTIHAD MUHAMMAD SYAHRUR (Analisis Kritis Terhadap Penggunaan Metode Ushul Fiqh Dan Fiqh) - Arsal, Arsal (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
In the contemporary world figure usul fiqh Muhammad Shahrur including a phenomenal figure and contradictory figure. This is due to the formulation of usul fiqh which manifest contradiction with the new model and the formulation of classical fiqh scholars. Likewise with the formula set out Shahrur shows fiqh law glitik invite observers. As for the criticism akibanya inevitable criticism leveled by scholars and only a limited number of characters and the only Islamic thinkers who show partiality to Shahrur. This paper will discuss how the model Shahrur usul fiqh and fiqh, then the author will try to provide responses to the method.